Effect of pharmacological modulation of myeloid-derived suppressor cell function on immune reactivity against mycobacterium tuberculosis. - Leukes, Vinzeigh (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2023.